2009
DOI: 10.1016/j.jpainsymman.2008.07.009
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Examining the Literature on Attitudes of Patients with Advanced Cancer Toward Research

Abstract: The attitudes of heterogeneous groups of cancer patients towards research have been studied extensively. Less is known about these attitudes in the advanced cancer population. Such patients may have differing attitudes for a variety of reasons, including burden of disease and social factors. This systematic review examines the literature on attitudes of patients with advanced cancer toward research and aims to define common themes. The following databases were searched electronically: CINAHL (1982-2007), the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…It is important to include the range of diagnoses that have palliative care needs as different patient groups can have distinct concerns regarding research. The gap in knowledge about cancer patients in the advanced stages of illness seems to be addressed since the review undertaken by [Todd et al 12]. Most of the studies identified in this review targeted the later stages of illness as concerns regarding research were expected to become more pronounced nearer to death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to include the range of diagnoses that have palliative care needs as different patient groups can have distinct concerns regarding research. The gap in knowledge about cancer patients in the advanced stages of illness seems to be addressed since the review undertaken by [Todd et al 12]. Most of the studies identified in this review targeted the later stages of illness as concerns regarding research were expected to become more pronounced nearer to death.…”
Section: Discussionmentioning
confidence: 99%
“…While it is necessary to consider the concerns of this debate there is little prospect of resolving the existing tensions by argumentation alone. Systematic reviews have appraised the evidence regarding advanced cancer patients’ attitudes towards research [12] and on palliative care patients’ and carers’ views about research in palliative care [13]. This study broadens the scope by undertaking a critical interpretive synthesis (CIS) [14] across this field in order to synthesise existing empirical data on the attitudes and values regarding participation held by all stakeholders involved in palliative care research.…”
Section: Introductionmentioning
confidence: 99%
“…Altruism is a commonly cited motive for trial participation [26-28], where participants take part in research for the benefit of others regardless of any benefit for themselves. There is a concern that the use of incentives may undermine altruistic reasons for participation.…”
Section: Discussionmentioning
confidence: 99%
“…‘Gatekeeping’ (ie, preventing access to potential research subjects) by clinical staff has also been cited as a problem in palliative care research studies 34 As a result, and despite there being evidence that palliative care patients and their carers are frequently in favour of participating in research,5 6 many studies fail to obtain their objective due to difficulties with recruiting the required sample size 7…”
Section: Introductionmentioning
confidence: 99%
“…Other reports of researchers’ experience have involved far fewer patients. A systematic review6 identified 11 papers investigating the attitudes of patients with advanced cancer to participation in research studies. The median sample size for these studies was 33 subjects and the largest study included 214 participants.…”
Section: Introductionmentioning
confidence: 99%